Acute Myocardial Infarction in a Patient with Two-Vessel Occlusion and a Large Lambl’s Excrescence - Alfredo Pizzuti; Francesco Parisi; Luciano Mosso; Francesca Cali’ Quaglia; Antonino Tomasello (Case Reports in Cardiology)
A 59-year-old man underwent an echocardiography study after myocardial infarction and it showed a thin, mobile mass attached to the aortic valve. A diagnosis of Lambl’s excrescence (LE) was suspected. Coronary occlusion as a consequence of embolism of LE’s material could not be excluded and the patient underwent surgical excision. Histology confirmed the diagnosis; however a differential diagnosis with papillary fibroelastoma could not be established because both of these structures are histologically indistinguishable. A brief survey of the literature is presented. Evidence-based recommendations for treatment have not been established yet.